The design of auto-tuning capacitive power transfer for rotary applications using phased-locked-loop - N. Nabila; Shakir Saat; Y. Yusop; M.S. M Isa; A.A. Basari (Institute of Advanced Engineering and Science, 2019)
Wireless power transfer (WPT), through the transmission of contactless energy, is not only being used for charging batteries in smartphones, but it is also being increasingly used in the field of industrial applications. The capacitive based approach is utilized in this paper because of its ability to transmit power in a metal surrounding environment where the inductive-based approach failed to perform. This work focuses on the coupling study of a rotary CPT application where the power supply is stationary while the load rotates and therefore allows the load to rotate 360o free rotation. The Class E MOSFET power inverter is used here due to its ability to achieve high efficiency compared to other class of converters at high frequency. The prototype of the CPT for rotary application has also been successfully developed with disk plate thickness of 1mm-2mm. Overall, the developed CPT system for rotary application is able to deliver 5.5Watt with 83.33% efficiency. To enhance the power efficiency and ZVS conditions, a self-tuning circuit using phased-locked-loop has been proposed in this paper. The efficiency of the developed system with self-tuning circuit is increased to 97.%.